Changing Macroeconomic Dynamics at the Zero Lower Bound. Issue 3 (3rd July 2019) - Liu, Philip; Theodoridis, Konstantinos; Mumtaz, Haroon; Zanetti, Francesco
ABSTRACT: This article develops a change-point VAR model that isolates four major macroeconomic regimes in the US since the 1960s. The model identifies shocks to demand, supply, monetary policy, and spread yield using restrictions from a general equilibrium model. The analysis discloses important changes to the statistical properties of key macroeconomic variables and their responses to the identified shocks. During the crisis period, spread shocks became more important for movements in unemployment and inflation. A counterfactual exercise evaluates the importance of lower bond-yield spread during the crises and suggests that the Fed's large-scale asset purchases helped lower the unemployment rate by about 0.6 percentage points, while boosting inflation by about 1 percentage point.